Outcome of Surgical Treatment in the Management of Tubercular Cervical Lymphadenopathy: An Experience in NIENT, Dhaka (Bangladesh Journal of Otorhinolaryngology, 2022)
Objectives: To observe the necessity and effectiveness of the surgical intervention as a last measure in management of tubercular cervical lymphadenopathy. Another objectives are to identity the various presentation of extra pulmonary cervical tuberculosis in our country, patterns as well as causes of recurrence and resistance, type of surgery done in tubercular cervical lymphadenopathy and complications after surgery.Materials and Methods: This prospective observational study was carried among 52 patients of tubercular cervical lymphadenopathy attended in the outpatient department (OPD) and admitted into the inpatient department (IPD) of National Institute of ENT, Dhaka during the period of January 2017 to June 2018 of which first 12 months for treatment and follow up; and next 06 months exclusively for follow up, where patients of tubercular cervical lymphadenopathy were surgically treated along with standard antitubercular drugs.Results: Most of the patients 71.16% had fever and weight loss, 51.93% patients had multiple nodes at one level, 48.08% abscess and 9.62% sinus, most tubercular lymph nodes were present at level V 73.07% and in the left side 57.69% , 60% were Gene -Xpert positive. All patients were cured who had underwent surgery with no recurrence.Conclusion: A good number of patients of tubercular cervical lymphadenopathy necessitated neck dissection but patient compliance is a must in the management of the disease.Bangladesh J Otorhinolaryngol 2022; 28(1): 84-90